Overview of Sorawolio Community Knowledge and Attitudes About Scabies - Aurellya Syalzabillah; Evi Mustiqawati; Wa Ode Syafriah (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Scabies remains a significant public health concern in tropical regions, particularly in densely populated communities where close contact facilitates transmission. In Sorawolio Subdistrict, Baubau, the high prevalence of scabies is presumed to be associated with insufficient community knowledge regarding its prevention and treatment. As a contagious parasitic skin disease, scabies can adversely affect physical comfort, social interaction, and overall quality of life. Therefore, understanding the level of community knowledge and attitudes toward scabies is essential to support effective prevention and control strategies. Objectives: This study aimed to assess the level of knowledge and attitudes of the Sorawolio community toward scabies and its prevention. Methods: A quantitative descriptive study design was employed. The study involved 61 respondents aged 5–25 years who had previously experienced or were currently experiencing scabies, resided in Sorawolio, and consented to participate in the study. Data collection was conducted from July 14 to August 14, 2024, using structured questionnaires designed to measure respondents’ knowledge and attitudes regarding scabies prevention and management. Data were analyzed descriptively using frequency and percentage distributions. Results: The findings indicated that 50 respondents (82%) demonstrated good knowledge regarding scabies, while 6 respondents (10%) had moderate knowledge and 5 respondents (8%) had poor knowledge. These results suggest that the majority of the community possesses an adequate understanding of scabies, potentially influenced by health education programs previously implemented in the area. Regarding attitudes, 59% of respondents exhibited positive and supportive attitudes toward preventive measures, indicating a generally favorable disposition toward scabies control practices. However, the presence of respondents with limited knowledge reflects existing gaps in information dissemination. Conclusion: Overall, the majority of respondents in Sorawolio demonstrated good knowledge and positive attitudes toward scabies prevention. Nevertheless, a proportion of the community still exhibits insufficient understanding, underscoring the need for sustained health education initiatives and targeted outreach programs to enhance awareness and promote comprehensive preventive behaviors across the broader population. Keywords: scabies; knowledge level; community attitude; health education; disease prevention